Why did the apple fall? A new model to explain Einstein's gravity. (2nd November 2016) - Stannard, Warren; Blair, David; Zadnik, Marjan; Kaur, Tejinder
Abstract: Newton described gravity as an attractive force between two masses but Einstein's General Theory of Relativity provides a very different explanation. Implicit in Einstein's theory is the idea that gravitational effects are the result of a distortion in the shape of space-time. Despite its elegance, Einstein's concept of gravity is rarely encountered outside of an advanced physics course as it is often considered to be too complex and too mathematical. This paper describes a new conceptual and quantitative model of gravity based on General Relativity at a level most science students should be able to understand. The model illustrates geodesics using analogies with paths of navigation on the surface of the Earth. This is extended to space and time maps incorporating the time warping effects of General Relativity. Using basic geometry, the geodesic path of a falling object near the surface of the Earth is found. From this the acceleration of an object in free fall is calculated. The model presented in this paper can answer the question, 'Why do things fall?' without resorting to Newton's gravitational force.